The UK parliament - Grant, Moyra (Politics study guides., 2009)
This topical and accessible introductory guide to the workings of the UK's Westminster Parliament outlines the history, structure and functions of the Parliament and provides a topical evaluation of how well those functions are performed. Special attention is paid to the relationships the Parliament has with the government, the EU, devolved bodies, and the courts. There is also an analysis of the impact of recent and possible future Parliamentary reforms.